Factors associated with clinical research participation among Medicare beneficiaries with prostate cancer in the United States - Ryan A. Hankins; Alysha M. McGovern; Abimbola O. Williams; Virgil H. Simons; Sean P. Collins; Deepak Kumar (Frontiers in Oncology, 2026)
Introduction Clinical research participation among patients with prostate cancer remains limited, and demographic, clinical, and contextual factors may influence opportunities for participation. Although disparities in prostate cancer diagnosis and treatment are well documented, less is known about the factors associated with clinical research participation in this population. This study examined patient-level and contextual factors associated with clinical research participation among older Medicare beneficiaries with prostate cancer. Methods A retrospective claims-based analysis was conducted using the Medicare 5% Standard Analytical Files to identify men aged ≥65 years with a healthcare encounter for prostate cancer between January 1, 2016 and December 31, 2021. Clinical research participation was identified using the International Classification of Diseases, Tenth Revision, Clinical Modification diagnosis code Z00.6 (“Encounter for examination for normal comparison and control in clinical research program”). Deidentified patient-level data were linked to 2020 county-level social determinants of health (SDOH) data from the Agency for Healthcare Research and Quality database. Multivariable logistic regression models were used to evaluate demographic, clinical, and county-level contextual factors associated with clinical research participation. Results A total of 107,250 Medicare Fee-for-Service (FFS) beneficiaries with prostate cancer were identified, representing approximately 2.145 million FFS beneficiaries after standard extrapolation. Among this cohort, 4,361 (4.07%) beneficiaries had documented clinical research participation, corresponding to approximately 87,220 beneficiaries after extrapolation. Compared to beneficiaries without documented research participation, beneficiaries participating in clinical research were younger, more often White, had higher Charlson Comorbidity Index (CCI) scores, and higher rates of metastatic disease. Residence in counties with higher socioeconomic indicators, including higher median household income, lower unemployment, higher educational attainment, and greater internet access was also associated with clinical research participation. After controlling for age, race, and CCI score, adjusted analyses identified several patient-level clinical and geographic characteristics, as well as county-level contextual characteristics, associated with clinical research participation, including metastatic disease, census region, county-level median household income, and county-level median distance to the nearest emergency department. Discussion These findings suggest that patient- and community-level factors may influence participation in clinical research. Targeted efforts to reduce structural and geographic barriers may help promote more equitable participation in clinical research among prostate cancer patients.